The Advantages of Labor Turnover: an Illustrative Case - Bezanson, Anne (Quarterly Journal of Economics, 1928)
The Philadelphia tapestry manufacture, 450.—The mills classed in Groups A, B, C, 452. — Hourly and weekly earnings at different mills compared, 453.—Entrances to Class A mills, 455.—Entrances to Class B mills, 459.—Entrances to Class C mills, 461.—Conclusion, 463.